Perubahan status gizi pada anak dengan leukemia limfoblastik akut selama pengobatan - Wolley, Nikmatiah G.A.; Gunawan, Stefanus .; Warouw, Sarah M. (e-CliniC, 2016)
Abstract: Acute lymphoblastic leukemia (ALL) is the most common malignancy diagnosed in children. Study of malnutrition prevalence in children with cancer is determined by nutritional status in the early diagnosis. This is important because it can affect patient’s progress before the treatment begins. This study aimed to determine the nutritional status alteration in children with ALL during treatment. This was a descriptive analytical study with a cohort-restrospective design in ALL patients during treatment at Pediatric Department of Prof. Dr. R. D. Kandou Hospital Manado during period January 2006 to August 2013. Data were obtained from medical records of Prof. Dr. R. D. Kandou Hospital Manado. There were 31 respondents suffered from ALL at the age of 1 to 11 years old; males were more frquent than females. There were 17 respondents at standard risk while 14 respondents were at high risk. The results result of paired t-test showed that t-value < table value. Conclusion: There was a significant increase of nutritional status in children with acute lymphoblastic leukemia during treatment Keywords: acute lymphoblastic leukemia, standard risk, high risk, nutritional status Abstrak: Leukemia Limfoblastik Akut (LLA) merupakan keganasan yang paling sering didiagnosis pada anak-anak. Studi prevalensi malnutrisi pada anak-anak dengan kanker ditentukan oleh status gizi pada awal diagnosis. Hal ini penting karena dapat berpengaruh pada perkembangan pasien sebelum pengobatan dimulai. Penelitina ini bertujuan untuk mengetahui perubahan status gizi pada anak dengan LLA selama pengobatan. Jenis penelitian ini deskriptif analitik dengan metode studi kohort-retrospektif terhadap pasien LLA selama pengobatan di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado selama periode Januari 2006 – Agustus 2013. Sumber data didapatkan dari rekam medik di RSUP Prof. dr. R. D. Kandou Manado. Didapatkan 31 sampel yang menderita LLA pada usia 1-11 tahun, laki-laki lebih banyak menderita LLA. Terdapat 17 sampel dengan risiko standar dan 14 sampel dengan risiko tinggi. Hasil analisis t-berpasangan menunjukan nilai t-hitung<nilai tabel. Simpulan: Terdapat peningkatan status gizi secara bermakna pada anak dengan leukemia limfoblastik akut selama pengobatan.Kata kunci: leukemia limfoblastik akut, risiko standar, risiko tinggi, status gizi